Analisis Tindak Tutur Direktif Tayangan “Si Bolang” di Youtube Edutainment Trans 7 Official dan Rekomendasinya Sebagai Bahan Ajar pada Teks Laporan Percobaan di Kelas IX - Wiratama, Aditya Dwi; Muhtarom, Imam; Syafroni, Roni Nugraha (Peneliti.net, 2024)
This research uses speech act theory according to Prayitno (2011:41) that directive speech acts do not only function to inform something. Directive speech acts have a very important role in everyday communication and are used to achieve various goals in social interactions. The research carried out was related to the analysis of directive speech acts in the